The Role of Job Burnout, Perceived Social Support and Psychological Hardiness in Predicting Quality of Life of Nurses - Z Rajaei; H Shafizadeh; N Babaeiamiri; A Amirfakhraei; J Ashoori (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: Appropriate quality of life not only is determined by disease, but also is depends to psychological condition such as job burnout, perceived social support and psychological hardiness. The research aim was to investigate the role of job burnout, perceived social support and psychological hardiness in predicting nurses' quality of life. Materials & Methods: The study was descriptive-analysis from type of correlation. The statistical population was including all nurses in Tehran affiliated hospitals in 2015. By multistep cluster sampling method, 400 nurses were selected. The study instruments were the Maslach & Jackson job burnout, Zimet & et al perceived social support, Kobasa psychological hardiness and World Health Organization quality of life questionnaires. Data analysis was performed in SPSS V.15 using coefficient Pearson correlation and multivariate regression analysis using Enter model. Results: The findings showed that Job burnout (r=-0/39) had a significant negative relationship with nurses' quality of life also perceived social support (r=0/61) and psychological hardiness (r=0/45) showed a significant positive relationship with nurses quality of life (P<0/01). In a predictor model, job burnout, social support and psychological hardiness could predict 59/3 percent of nurses' quality of life alterations (R2=0/593). Conclusion: The job burnout, perceived social support and psychological hardiness variables had effective roles in predicting nurses' quality of life. Hence, it is proposed that counselors, therapists and planners consider the symptoms of these variables and design appropriate programs to improve nurses' quality of life.